(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper aims at investigating the relationship between vulnerability and artificial intelligence systems in law, following a philosophical-legal reading. The investigation therefore questions, firstly, the existence of vulnerability, in an attempt to clarify its definitions and ways of grasping it. Secondly, the paper proposes the example of pain, dwelling on its ontological and (onto-)epistemological profiles, nominating liberalised naturalism as the appropriate realist framework in identifying it. Thirdly, by investigating informational structural realism, the partial incompatibility between the ontological structure presupposed by vulnerability, on the one hand, and artificial intelligence systems, on the other, is highlighted.